2021
DOI: 10.3390/ijms22189671
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Antihyperalgesic and Antitumor Effects of Gabapentin in a Murine Cancer Pain Model

Abstract: Cancer pain may be the consequence of physical nerve compression by a growing tumor. We employed a murine model to study whether gabapentin was able to regulate tumor growth, in addition to controlling hyperalgesic symptoms. A fluorescent melanoma cell line (B16–BL6/Zs green) was inoculated into the proximity of the sciatic nerve in male C57BL/6 mice. The tumor gradually compressed the nerve, causing hypersensitivity. Tumor growth was characterized via in vivo imaging techniques. Every other day, gabapentin (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Although bona fide targets remain elusive at present, Gbp could be one drug option for the treatment of TSC. A recently reported antimelanoma effect of Gbp in a tumor implantation system might offer an existing model for the in vivo analysis to examine the efficacy of Gbp (Brito et al, 2021). Because combined effects with rapamycin were observed in growth assays in vitro, we anticipate that treatment with Gbp and rapamycin at a reduced dose could be a useful strategy for avoiding drug adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although bona fide targets remain elusive at present, Gbp could be one drug option for the treatment of TSC. A recently reported antimelanoma effect of Gbp in a tumor implantation system might offer an existing model for the in vivo analysis to examine the efficacy of Gbp (Brito et al, 2021). Because combined effects with rapamycin were observed in growth assays in vitro, we anticipate that treatment with Gbp and rapamycin at a reduced dose could be a useful strategy for avoiding drug adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…No study has examined the relationships between MGB and the expression of cell cycle–related molecules, such as cyclins and CDKs. Gabapentin, another voltage-gated calcium channel α2δ unit ligand, inhibits transplant tumor growth of a melanoma cell line 3 ; however, its detailed antiproliferative effects were not described. Although whether the expression of cyclins and CDKs is modulated by MGB through the α2δ1 and α2δ2 subunits is still unclear, our results suggest that the upregulation of cyclins and CDKs would be one of the pro-proliferative mechanisms of MGB.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have verified the anticancer effects of Gabapentin in recent years. Gabapentin may achieve anti-melanoma effects in mice by reducing cell proliferation, CCL2 production, and calcium influx ( 68 ). In recent years, it has been demonstrated that thiamine-dependent enzymes (TDEs) are frequently tumor-related targets due to their control of metabolic pathways that are frequently altered in cancer.…”
Section: Discussionmentioning
confidence: 99%